TINJAUAN HUKUM ATAS PERATURAN DIREKTUR JENDERAL PAJAKNOMOR PER-17/PJ/2015 TENTANG NORMA PENGHITUNGANPENGHASILAN NETO TERHADAP BEBERAPA PEKERJA BEBAS TERTENTU - Prasetiyo, Hari; Imadudiin, Shariif (Jurnal Vokasi Indonesia, 2019)
This research reviewed on the Regulation of the Director General of Tax No. PER-17/PJ/2015 on Norms of Net Income Calculation of several specific self-employment. The discussions in this research included discussion on the arrangement in the Regulation of the Director General of Tax No. PER-17/PJ/2015 towards Profession of Taxpayer like Writer, Notary, and Doctor and the implementation of the regulation based on the principle of legal certainty towards Taxpayer of Writer, Notary, and Doctor. The research method used in this research is in the form of normative-juridical research with descriptive-analytic research type. On the implementation of the Regulation of the Director General of Tax No. PER- 17/PJ/2015, there are two problems which are the differences of interpretation in the regulation between Directorate General of Taxes and the Primary Tax Office which resulted in issuing a press release and a circular relating to the problem. The second problem is the ignorance of the taxpayer regarding the regulation. The first problem on the implementation of the regulation will be reviewed by the principle of legal certainty in the tax law. The result in this thesis is that the arrangement on Norms of Net Income Calculation towards Taxpayer of Writer, Notary, and Doctor Profession has been regulated in the Regulation of the Director General of Tax No. PER-17/PJ/2015 based on their Business Field Classification. Moreover, there is a legal uncertainty in the Regulation of the Director General of Tax No. PER-17/PJ/2015 caused by a circular letter related to the regulation.